Implementasi Sistem Penjaminan Mutu Internal dalam Meningkatkan Mutu Pendidikan di MIN 1 Rejang Lebong - Okta Ria Enes, Utami; Kusen, Kusen; Wanto, Deri (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2024)
ABSTRACTInternal quality assurance is carried out with reference to national educational standards in order to realize the educational goals of the country. Internal quality is currently used in basic and secondary education in addition to universities. This study aims to identify and explain the internal quality system cycle's implementation. Data collecting methods include observations, interviews, and documentary research. According to the findings of this study, Darul Farah Cihampelas Secondary School has implemented the following quality improvement activities in accordance with the stages of the SPMI cycle: first, a school self-evaluation based on the education quality report; second, quality improvement planning through the creation of a quality assurance committee and a re-analysis of the results of the school self-evaluation; third, implementation of quality improvement; and fourth. The evaluation of educational quality comes in second. Quality strategy for the fifth fiscal year, evaluation following quality improvement, and quality improvement results. Implementing internal quality assurance will have an influence on the development of more creative teaching methods, student and school performance, internal and external customer happiness, and the fulfillment of the eight National Education Standards.Â